Study on the wind-field characteristics over a bridge site due to the shielding effects of mountains in a deep gorge via numerical simulation. Issue 14 (October 2019) - Mingjin, Zhang; Jisheng, Yu; Jingyu, Zhang; Lianhuo, Wu; Yongle, Li
To investigate the shielding effects of mountains in front of a bridge on the wind field at the bridge site in an area with complex topography, a numerical simulation model of the bridge site, which is located in a deep cut V-shaped gorge, was conducted by a computational fluid dynamics method. In this study, taking the shielding effects of mountains in front of the bridge into consideration, the mean velocity, wind attack angle, wind profile, and wind direction angle under different flow cases were calculated and compared. The spatial distribution characteristics of the wind field in an area with complex topography considering shielding effects are presented. The calculation results indicate that the characteristics of the wind field near the mountain at the bridge site are affected by the mountain and the direction of the incoming flow. The shielding effects of the mountain on the eastern side of the bridge are very different under different flow directions. The wind load distribution along the girder is severely uneven in some cases due to a local cyclone existing around the girder. The conclusions of this study provide a basis for improved wind resistance designs of bridges.